Ulumul Quran Fondasi Ilmu Memahami Al-Quran Secara Komperhensif - Zahrotul Kamilah Ansori; Amanah Giovani Visi Yuti Viona; Deka Abi Dafissa; Hakmi Hidayat (GLOBAL SCIENTS PUBLISHER, 2025)
Ulumul Qur'an is a branch of science in Islam that specifically studies various aspects related to the Qur'an. Areas of focus in this study include the history of the revelation of the Qur'an, its recitation techniques (qira'at), how to interpret it, as well as the social and historical background in the decline of various verses. The purpose of this article is to provide a complete explanation of the definition, scope, purpose, and journey of the development of this science from the time of the Prophet Muhammad SAW to the time of the companions and tabi'in. With an understanding of these elements, it is hoped that Muslims can explore the meaning of the Qur'an more deeply and contextually, so that they can apply its teachings in their daily lives. This research confirms that Ulumul Qur'an plays a very significant role, not only in an academic context, but also in answering religious and social challenges in modern times.